Anoxic continental surface weathering recorded by the 2.95 Ga Denny Dalton Paleosol (Pongola Supergroup, South Africa). (15th February 2021) - Heard, Andy W.; Aarons, Sarah M.; Hofmann, Axel; He, Xiaoqing; Ireland, Thomas; Bekker, Andrey; Qin, Liping; Dauphas, Nicolas
Abstract: Iron mobilization during continental weathering was pervasive before the Great Oxidation Event (GOE) that started at around 2.43 billion years (Ga) ago, due to the soluble nature of reduced iron. However, various geochemical proxies indicate transient oxygenation during deposition of the Mesoarchean (∼2.95 Ga) Pongola Supergroup, South Africa, which suggests that continental weathering could have also occurred under transiently oxic conditions before the GOE. We analyzed trace elemental and Fe, Ti, and Cr isotopic compositions of the ca. 2.95 Ga Denny Dalton paleosol in the Pongola Supergroup to better understand continental weathering and redox conditions in the ancient critical zone, and the nature of geochemical fluxes from the continents to the oceans and marine sediments. Iron isotope systematics are consistent with a model where Fe was released during intense leaching from the paleosol to concentrate in Fe-rich groundwaters in the deeper part of the soil horizon. We show for the first time that Fe isotopic fractionation during Mesoarchean continental weathering was limited, and Fe enrichments and depletions are coupled with those of divalent transition metals, Co, Ni, and particularly Zn. This suggests that Fe redox cycling was not involved in paleosol formation, and Fe 2+ was mobilized under anoxic conditions. Chromium isotopes are also unfractionated relative to the parent igneous rock in this paleosol, which precludes removal of isotopically heavy Cr 6+ and thus supports anoxic continental weathering. We show that previously reported Cr isotopic fractionation in another Denny Dalton paleosol profile does not follow a Cr 6+ leaching trend, but instead scales with Cr enrichment and may reveal Cr enrichment from post-burial fluids. Thus, there is no clear evidence for an oxidative continental weathering during deposition of the Pongola Supergroup. Titanium isotopes are not significantly fractionated in the paleosol, suggesting that continental weathering and erosion in the Archean did not fractionate Ti isotopes. Similarly, Ni/Co and Th/Sc ratios are reasonably conserved, which validates their use as a robust proxy for upper continental crust composition in shales, whereas La/Sc, Cr/Zn and Cr/U ratios are highly variable relative to the provenance composition, which suggests that caution should be used when applying these ratios in shale studies of the ancient upper continental crust composition.